Vibration Characteristic Analysis of High-speed Train Gear Transmission System Under Track Irregularity - Qian Xiao; Yuqi Cheng; Xu Xu (Jixie chuandong)
In order to analyze the vibration characteristics of high-speed train gear transmission system under the influence of track irregular excitation， the dynamics software SIMPACK is used to establish a vehicle dynamic model including the gear transmission system， and the measurement points are arranged inside the large and small gears respectively. Dynamics simulation experiments under no track irregularities and conditions with track irregularities can obtain the vibration acceleration of large and small gears at a speed of 250 km/h for high-speed trains. The horizontal， vertical and vertical vibration acceleration amplitudes of the large and small gears are analyzed in frequency domain， and then the vibration amplitude and frequency spectrum distribution of the gear transmission system in the presence and absence of track irregularities are compared and analyzed. The results show that due to the influence of track irregular excitation， the lateral， longitudinal and vertical vibrations of the high-speed train gear transmission system are strengthened， and the vibration acceleration increases significantly， among which the vertical vibration acceleration has the largest amplitude change. The vibration frequency of the gear transmission system is mainly concentrated in 0~400 Hz. The lateral vibration of the pinion and the large gear is affected by the track irregularity， but the longitudinal vibration of the pinion is slightly smaller than that of the large gear， and the vertical vibration of the pinion is slightly larger than that of the large gear.